Effect of Red Flags and Competence on Fraud Detection with Professional Skepticism as Moderation - Gusti Ngurah Adhitya Putra Utama; Yadhurani Dewi Amritha (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study investigates the impact of auditor competence and red flag awareness on fraud detection ability, examining the moderating role of professional skepticism. As fraudulent financial reporting poses a critical threat to the integrity of financial disclosures and stakeholder trust, understanding the key factors influencing an auditor's detection capabilities is essential. This study employed a quantitative approach, gathering data from auditors at Public Accounting Firms (KAP) in Bali Province via a four-point Likert scale questionnaire. The data were subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings indicate that both auditor competence and an awareness of red flags significantly and positively enhance fraud detection capabilities. Conversely, professional skepticism, when analyzed for its direct influence, demonstrated a significant negative effect on this ability. Furthermore, skepticism exhibited a complex moderating role: it significantly weakened the positive relationship between competence and fraud detection, while not significantly moderating the link between red flags and detection ability. These results provide crucial theoretical contributions by revealing the nuanced and sometimes counter-intuitive role of professional skepticism. Practically, they inform policy for audit firms and regulatory bodies, suggesting that while fostering competence and red flag awareness is vital, the application of skepticism requires a more sophisticated and refined approach to truly enhance audit quality and overall fraud detection effectiveness.